Using Ethnography in Psychological Research: Challenges and Opportunities - Ermida Simanjuntak; Suryanto Suryanto; Wiwin Hendriani (Faculty of Psychology Universitas Gadjah Mada, 2022)
Ethnography has gained more popularity in psychological research in recent years. As one of the qualitative traditions, ethnography is best to describe the behaviour of group and group member deeply rooted in its culture and cultural values. This paper presents a literature review on the role, challenges, and opportunities in adopting ethnography in psychological research. Study examples are presented within which,types of ethnographical design to explore new psychological phenomena are discussed. Continous self-reflection for both researchers and participants and researcher’s flexibility of using data collection methods informed by researcher’s positionality and engagement are suggested to further advance rigour in the study findings.